Pengaruh Pelatihan Kerja, Kreativitas Dan Motivasi Terhadap Kinerja Karyawan Pada PT. PWI - Nur Laila Zulfa; Sri Padmantyo (POLITEKNIK LP3I JAKARTA, 2023)
The purpose of this study is to identify, analyze, and demonstrate the impact of job training, motivation, and creativity on employee performance at PT PWI. This study uses quantitative research techniques and is an applied research. In accordance with the requirements of the Slovin formula, this study used up to 144 respondents from a sample of field workers. Multiple linear regression analysis, partial test (t test), and coefficient of determination are the types of hypothesis testing used in the data analysis of this study. Data processing in this study used the Statistical Program for Social Science (SPSS). The results obtained in this study explain that the employee performance variable has a positive effect on the creativity variable, and motivation on employee performance at PT PWI. The results of this study have implications that focus on creativity, indicating that creative employees must be able to innovate in finding new opportunities, doing new things, taking ideas from things around them, being broad-minded, capturing feedback from consumers because this company is engaged in manufacturing sports shoes.Keywords: Job Training, Creativity, Motivation, Employee Performance